Biocompatible Zn(II) Adsorption Using Tofu-Waste Polyurethane: Effects on Moisture, Ash Content, and pH of Oysters - rita sunartaty; Irmayadani (Postgraduate, University of Mataram, 2025)
This study aimed to evaluate the performance of a tofu-dregs-based polyurethane adsorbent in removing Zn(II) ions and to examine its effects on the moisture content, ash content, and pH variation in oysters (Crassostrea spp.), as well as to assess compliance with Indonesian National Standards. The method used in this study involved exposing fresh oysters to ZnSO₄ solutions at concentrations of 2, 4, and 6 ppm for 60 minutes in the presence of the composite adsorbent. Moisture content was determined gravimetrically at 105 °C, ash content by dry ash at 550 °C, and pH was monitored throughout the contact period. The results showed that the moisture content of fresh oysters remained stable at 89–91% before and after adsorption, while dried oyster samples had reduced moisture levels of 11.0–11.8%, meeting the ≤ 12% limit for dried products. The ash content of the adsorbent increased from 3.00% to 7.80–9.60%, indicating effective retention of Zn(II) ions, whereas the ash content of oysters remained relatively constant at 1.90–1.96%, suggesting minimal accumulation of metal ions in the tissues. A gradual increase in solution pH during the adsorption process confirmed chemical interactions between Zn²⁺ ions and functional groups on the adsorbent surface. These findings demonstrate that the tofu-dregs-based polyurethane adsorbent is effective for Zn(II) removal while maintaining oyster quality within national safety standards, highlighting its potential as an environmentally friendly material for heavy-metal remediation.